RANCANG BANGUN APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DALAM MEMBANGUN LOYALITAS PELANGGAN UMKM (Studi Kasus: Usaha Cistik Resep Eyang) - Any Saroh Dwisono (2022)
The development of technology, especially the internet, is used not only for the exchange of information, but also for business processes that have changed the company's business activities. In business, company owners should take advantage of this moment to add value to their business development. One of the mistakes in the UKM business is that there is still not much emotion involved in the customer, so the current promotion strategy of UKM players is only limited to introducing the advantages of their products without understanding the needs and feelings of customers. This marketing challenge is a breakthrough method used by UMKM to maintain good relationships with customers and build their loyalty through knowledge and quick response to customer needs, how to keep customers loyal to the products or services offered and how to manage customer relationships (Customer Relationship Management). CRM applications can help UMKM, one of which is Cistik Resep Eyang in developing products based on complete knowledge of customer expectations, market dynamics and between competitors. How to implement the CRM idea with a website application which can provide information related to customer needs as an increase in customer satisfaction. The system built is a website-based Electronic Customer Relationship Management (e-CRM). So it is hoped that there good communication relationship with customers from stakeholders, especially management, which aims as a solution to improve service quality and maintain customer loyalty Cistik Resep Eyang.